ANALISIS YURIDIS TERHADAP PEMBUKTIAN TURUT SERTA TINDAK PIDANA PEMALSUAN SURAT DALAM PERKARA NOMOR 423/PID.B/2017.PN.PBR - Endang Selawati; Emilda Firdaus; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Counterfeiting is a type of violation of truth and trust, with the aim of obtaining benefits for oneself or others. A regular association of life in a well-developed society cannot take place without the guarantee of the truth of some of the evidence of letters and other documents. Therefore falsification can be a threat to the survival of the community.This research is classified into normative legal research, namely research conducted by examining library materials (secondary data) or library research. Meanwhile, when viewed from its nature, the writing of this research is descriptive, which means the research is intended to provide a detailed, clear and systematic description of the main problems of the study.From the results of the research that the author did, it can be concluded as follows: Proof of participating in the crime of falsification of letters in case number 423 / Pid.B / 2017 / PN.Pbr that the Defendant was proven to have committed the falsification based on the evidence presented by the Public Prosecutor. The evidence is witness testimony, Defendant's Statement and Evidence in the form of a fake letter that has a stamp and the signature of the Riau High Prosecutor's Office. The element of participating in the criminal offense of forgery of letters in the offense of inclusion of Criminal Liability for Participants and Committing Acts of Falsification of Letters (Seals and Signature of the Riau High Prosecutor's Office) in Case No. 423 / Pid.B / 2017 / PN.Pbr that perpetrators impose sanctions Article 263 Paragraph (1) Jo Article 55 of the Criminal Code with the threat of imprisonment for 4 (four) months.Keywords: Juridical Analysis - Also Participating - Criminal Acts - Falsification of Letters